Evaluation of Electrospun Nanofibrous Structures for Drug Release Application - Haroosh, Hazim Jasim Mohammed; Dong, Yu (The Institution of Chemical Engineers (IChemE), 2014)
Biopolymers show the excellent biodegradability and efficient release sustainability for encapsulated drugs. In particular, electrospun polymer or composite fibre mats provide greater benefits owing to their competitive release properties and large specific surface area. This research work focused on electrospun nanofibres derived from poly(e-caprolactone) (PCL), poly(lactic acid) (PLA) and PCL/ magnetic nanoparticles (MPs) solutions by carrying a therapeutic compound tetracycline hydrochloride (TCH) with the potential use for medical applications. The material systems were examined to evaluate how composite constituents affected the surface morphology with the aim of drug release control. It has been found that the fibre diameter decreased considerably with the addition of TCH drug. The average fibre diameter was also reduced with additional MPs due to enhanced solution conductivity. Furthermore, Fourier transform infrared spectroscopy (FTIR) proved the successful encapsulation of TCH drug. Over short-term periods, the TCH release from PCL nanofibres was higher than PCL/ MPs and PLA nanofibres; whereas, on a long-term run, TCH release from PCL became slower owing to its high degree of crystallinity. The TCH release kinetics of PCL/ TCH nanofibres were better estimated by Zeng model when compared with PLA/TCH counterparts.